Technological innovation for sustainability Second IFIP WG 5.5/SOCOLNET doctoral conference on computing, electrical and industrial systems, DoCEIS 2011, Costa de Caparica, Portugal, February 21-23, 2011. Proceedings - Camarinha-Matos, Luis (IFIP Advances in Information and Communication Technology, 2011)
This book constitutes the refereed proceedings of the Second IFIP WG 5.5/SOCOLNET Doctoral Conference on Computing, Electrical and Industrial Systems, DoCEIS 2011, held in Costa de Caparica, Portugal, in February 2011. The 67 revised full papers were carefully selected from numerous submissions. They cover a wide spectrum of topics ranging from collaborative enterprise networks to microelectronics. The papers are organized in topical sections on collaborative networks, service-oriented systems, computational intelligence, robotic systems, Petri nets, sensorial and perceptional systems, sensorial systems and decision, signal processing, fault-tolerant systems, control systems, energy systems, electrical machines, and electronic